Optimization of immersion frequency and medium substitution on microtuberization of Chlorophytum borivilianum in RITA system on production of saponins - Ashraf, Mehdi Farshad; Abdul Aziz, Maheran; Stanslas, Johnson; Abdul Kadir, Mihdzar (Elsevier, 2013)
In this study, different immersion times were compared for optimization of Chlorophytum borivilianum microtuber production in a RITA (Récipient à Immersion Temporaire Automatique) system. Significantly higher mean number and length of microtubers and growth index were obtained (16, 52 mm and 16, respectively) with 15 min immersion in microtuberization medium (MM) for every 60 min rest period, and could eliminate the occurrence of hyperhydricity. The substitution of MM with liquid hormone-free MS (MSO) medium on week 6 of culture differed significantly in terms of mean number and length of microtubers and growth index compared to earlier substitution at week 3 with MSO but did not differ significantly in comparison to cultures maintained throughout the 9 weeks in MM. Comparison of total saponin of TIS-derived microtubers with tubers of field grown mother plant showed a 1.3-fold increase of saponin (≈21% diosgenin) in the microtubers. The above results hold a promising application of TIS for large scale production of microtubers and accumulated saponin in C. borivilianum.